Impacts of pre-treatment technologies and co-products on greenhouse gas emissions and energy use of lignocellulosic ethanol production - Pourbafrani, Mohammad; McKechnie, Jon; Shen, Timothy; Saville, Bradley A.; MacLean, Heather L. (Elsevier, 2014)
Life cycle environmental performance of lignocellulosic ethanol produced through different production pathways and having different co-products has rarely been reported in the literature, with most studies focusing on a single pre-treatment and single co-product (electricity). The aim of this paper is to understand the life cycle energy use and greenhouse gas (GHG) emissions implications of alternative pre-treatment technologies (dilute acid hydrolysis, ammonia fiber expansion and autohydrolysis) and co-products (electricity, pellet, protein and xylitol) through developing a consistent life cycle framework for ethanol production from corn stover. Results show that the choices of pre-treatment technology and co-product(s) can impact ethanol yield, life cycle energy use and GHG emissions. Dilute acid pathways generally exhibit higher ethanol yields (20 to 25%) and lower net total energy use (15 to 25%) than the autohydrolysis and ammonia fiber expansion pathways. Similar GHG emissions are found for the pre-treatment technologies when producing the same co-product. Xylitol co-production diverts xylose from ethanol production and results in the lowest ethanol yield (200 litres per dry t of stover). Compared to producing only electricity as a co-product, the co-production of pellets and xylitol decreases life cycle GHG emissions associated with the ethanol, while protein production increases emissions. The life cycle GHG emissions of blended ethanol fuel (85% denatured ethanol by volume) range from -38.5 to 37.2 g CO2eq/MJ of fuel produced, reducing emissions by 61% to 141% relative to gasoline. All ethanol pathways result in major reductions of fossil and petroleum energy use relative to gasoline, at least 47% and 67%, respectively. Pathways with electricity as the sole co-product use the least fossil energy All ethanol pathways studied meet the USA Energy Information and Security Act requirement of a 60% reduction in GHG emissions compared to gasoline for classification as a cellulosic biofuel; however, greater reductions are achievable through strategic selection of co-products.